2019
DOI: 10.1149/2.1301910jes
|View full text |Cite
|
Sign up to set email alerts
|

Composite Poly(norbornene) Anion Conducting Membranes for Achieving Durability, Water Management and High Power (3.4 W/cm2) in Hydrogen/Oxygen Alkaline Fuel Cells

Abstract: Alkaline fuel cells and electrolyzers are of interest because they have potential advantages over their acid counterparts. Highconductivity anion conducting membranes were analyzed and used in alkaline hydrogen/oxygen fuel cells. The membranes were composed of reinforced block copolymers of poly(norbornenes) with pendant quaternary ammonium head-groups. It was found that membranes with light cross-linking provided excellent mechanical stability and allowed very high ion exchange capacity polymers to be used wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
177
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 205 publications
(182 citation statements)
references
References 40 publications
3
177
0
2
Order By: Relevance
“…Experiential parameters for the DMA were set to 0.1% strain and a preload force of 0.01 N with a force track of 125%. [26] Electrode Fabrication Using GTXX Ionomers: GDEs were fabricated using a previously developed method [16,19] where a catalyst ink was made from the GTXX ionomers, DI H 2 O/isopropyl alcohol solvent, and Pt-based electrocatalysts. 40% Pt/C (Alfa Aesar HiSPEC 4000, Pt nominally 40 wt%, supported on Vulcan XC-72R carbon) was used at the cathode and 60% Pt-Ru/C (Alfa Aesar HiSPEC 10000, Pt nominally 40 wt%, and Ru, nominally 20 wt%, supported on Vulcan XC-72R carbon) was used at the anode.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiential parameters for the DMA were set to 0.1% strain and a preload force of 0.01 N with a force track of 125%. [26] Electrode Fabrication Using GTXX Ionomers: GDEs were fabricated using a previously developed method [16,19] where a catalyst ink was made from the GTXX ionomers, DI H 2 O/isopropyl alcohol solvent, and Pt-based electrocatalysts. 40% Pt/C (Alfa Aesar HiSPEC 4000, Pt nominally 40 wt%, supported on Vulcan XC-72R carbon) was used at the cathode and 60% Pt-Ru/C (Alfa Aesar HiSPEC 10000, Pt nominally 40 wt%, and Ru, nominally 20 wt%, supported on Vulcan XC-72R carbon) was used at the anode.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Mandal et al, reported highly conductive crosslinked poly(norbonene) membranes (198 mS cm −1 ) that showed no significant ionic conductivity loss over 1000 h in 1 m KOH at 80 °C. [7] Huang et al, used similar materials in AEMFCs, enabling very high peak power density to be achieved (3.4 W cm −2 ) under H 2 /O 2 reacting gases, [26] which was recently improved to 3.5 W cm −2 by using thinner membranes. [27] In this study, three poly(norbornene) tetrablock copolymer ionomers with different IEC, molecular weight, dispersity, and water uptake were synthesized and fully characterized for their physical and electrochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, over the past two years, a significant increase in the peak power density has been observed, [5][6][7][8][9] with state-ofthe-art AEMFCs having the ability to achieve values over 3 W cm À2 operating on H 2 /O 2 gas feeds. 10 Also, the performance stability of AEMFCs has improved dramatically during this time, with multiple groups reporting 500+ hour stability at low degradation rates (5-10%). [11][12][13][14] Now that AEMFC performance and stability has been enhanced to the point where their future deployment in real applications can be seriously contemplated, it is now an important time in AEMFC development to begin to answer some of the other lingering issues that have to date been mostly put aside in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the highest AEMFC performances reported to date are based on this fabrication method. 3,22 DMD-10 shows a maximum power density of 800 mW cm À2 (compared to DMD-5 and DMD-3), which is likely a result of the thicker membrane, leading to increased ionic resistance (42 mOhm cm 2 @ 2000 mA cm À2 ) and an earlier onset of mass transport losses. The increased mass transport losses can most probably be ascribed to the reduced water back diffusion from the anode to the cathode side caused by the thicker membrane, 12,23 since all other fabrication and operation parameters were kept the same.…”
Section: Electrochemical Propertiesmentioning
confidence: 97%
“…2 In particular in the past three years, the performance of AEMFCs has dramatically risen, surpassing 3 W cm À2 (under H 2 /O 2 conditions). 3 Although signicant progress has been made in the development of AEMFCs in the last decade, major challenges remain. 2 One issue is the sluggish HOR on the anode side, which, using platinum as a catalyst, is about two orders of magnitude slower than in acidic media.…”
Section: Introductionmentioning
confidence: 99%